Performance of steel plate shear walls with axially loaded vertical boundary elements. (April 2018) - Yu, Jin-Guang; Feng, Xiao-Tian; Li, Bo; Hao, Ji-Ping; Elamin, Ahmed; Ge, Ming-Lan
Abstract: This paper presents a study of the applicability of the flexibility coefficient limit for vertical boundary elements (VBEs) in steel plate shear walls (SPSWs). One 1/3-scale, one-bay, and two-storey SPSW specimen was tested under quasi-static cyclic loading. The specimen had the flexibility coefficient and axial load ratio of the VBEs of 2.2 and 0.3, respectively. The results show that axial loads on the VBEs exacerbate the failure of SPSW structure. At the drift ratio of 0.9%, VBEs subjected to the axial load of 0.3 f y A g exhibited considerable inward deformation equivalent to 1/400 of the column height. Besides, a finite element model (FEM) of SPSW structure was established and validated by test results. A parametrical study of SPSW specimens with various width-to-height ratios of infill steel plates and axial load ratios of VBEs was subsequently conducted by the FEM. The influence of VBEs with different axial loads on the structural performance of SPSWs was also discussed. Without considering the effect of axial load, the VBE flexibility coefficient limit of 2.5 is applicable for the SPSWs with the width-to-height ratio of 1.0 for the infill steel plate. However, with an increase of the width-to-height ratio of the infill steel plate, the development of the tension field tends to be inadequate, while the shear capacity and stress uniformity of the infill steel plate decrease. As a result, the flexibility coefficient limit of 2.1 is recommended for the design of VBEs in SPSW structures. Contrarily, considering the axial load effect, axial loads acting on the VBEs significantly decrease the shear capacity and stress uniformity of SPSWs with levels depending on the width-to-height ratio of infill steel plates and the flexibility coefficient of VBEs. To fully develop the tension field in infill steel plates for lateral resistance of SPSWs, axial load ratio, width-to-height ratio, and column flexibility coefficient should be taken into consideration in the design of SPSW structures. Highlights: Performance of steel plate shear walls (SPSWs) is experimentally investigated. Axial loads on vertical boundary elements (VBEs) exacerbate the failure of SPSWs. Parametric study of SPSW structure is conducted by finite element analysis. The flexibility coefficient limit for VBEs in SPSWs is recommended to be 2.1. Increasing axial loads on the VBEs reduces the shear strength of SPSWs.